When Intention Is Not Enough: Post-Adoption Use Behavior of Islamic Mobile Banking within the UTAUT2 Framework - Mu'tamim, Nurul; Dwita, Vidyarini (Economics, Business, Accounting & Society Review, 2025)
This research investigates the factors influencing usage behavior of the Muamalat DIN application, an Islamic mobile banking service provided by Bank Muamalat Indonesia in Padang City, by applying the UTAUT2 framework. Specifically, the study evaluates the effects of performance expectancy, effort expectancy, and facilitating conditions on users’ behavioral intention, as well as the impact of behavioral intention on actual usage behavior. Additionally, it examines the mediating role of behavioral intention and the moderating effect of user experience on the relationship between intention and use behavior. A quantitative research design was employed, with data collected through a survey of 105 Muamalat DIN users. The data were processed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings demonstrate that performance expectancy, effort expectancy, and facilitating conditions exert positive and significant influences on behavioral intention. Behavioral intention, in turn, significantly affects use behavior and serves as a mediator between the antecedent variables and actual application usage. Moreover, user experience significantly moderates the relationship between behavioral intention and use behavior, suggesting that the influence of intention diminishes as users accumulate greater experience. In summary, the sustained use of Islamic mobile banking services is largely shaped by users’ perceptions of usefulness, ease of use, and the availability of adequate supporting infrastructure. This study extends the UTAUT2 literature by offering a post-adoption perspective within the context of Islamic digital banking and provides practical insights for banks seeking to improve service quality and user experience in order to foster continued usage.